1989
DOI: 10.1007/bf01000041
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and 2-oxoglutarate as metabolic precursors of the transmitter pools of glutamate and GABA: Correlation of regional uptake by rat brain synaptosomes

Abstract: To more clearly define the roles of glutamine and 2-oxoglutarate as metabolic precursors of the transmitter pools of glutamate and GABA we have determined the relative rates at which these four substances, and adenosine and serotonin are accumulated by synaptosomes derived from twelve regions of the rat brain. Initial transport conditions and low substrate concentrations were used to maximize uptake by high-affinity systems, except the uptake of glutamine was determined at both low and high concentrations. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…These findings are consistent with the observation by Kaufman and Driscoll [14,29] that synthesized TCA cycle constituents or their metabolites are released in large amounts from homogeneous cultures of astrocytes, whereas the net release is much less in mixed neuronal-as trocytic cultures and with that by Shank and Campbell [30][31][32] that a-ketoglutarate is actively accumulated into synaptosomal preparations. Our experiments were the first direct demonstration that a-ketoglutarate itself can actually function as a precursor for transmitter gluta mate, but it had previously been shown by Kihara and Kubo [33] that the release of glutamate from a brain stem preparation is enhanced in the presence of a-ketoglu tarate in the incubation medium.…”
Section: T C a Cycle C Onstituents As P Re Cursors For Transm Itter Gsupporting
confidence: 81%
“…These findings are consistent with the observation by Kaufman and Driscoll [14,29] that synthesized TCA cycle constituents or their metabolites are released in large amounts from homogeneous cultures of astrocytes, whereas the net release is much less in mixed neuronal-as trocytic cultures and with that by Shank and Campbell [30][31][32] that a-ketoglutarate is actively accumulated into synaptosomal preparations. Our experiments were the first direct demonstration that a-ketoglutarate itself can actually function as a precursor for transmitter gluta mate, but it had previously been shown by Kihara and Kubo [33] that the release of glutamate from a brain stem preparation is enhanced in the presence of a-ketoglu tarate in the incubation medium.…”
Section: T C a Cycle C Onstituents As P Re Cursors For Transm Itter Gsupporting
confidence: 81%
“…Using 14 C-labeled substrates, glutamine has repeatedly been shown to be a GABA precursor [25,29,32,54,55]. From the present study using [U- 13 C]lactate and [U- 13 C]glucose to label the pool of TCA cycle intermediates, it may be suggested that glutamine predominantly has to be metabolized via the TCA cycle prior to synthesis of GABA (fig.…”
Section: Gaba Synthesismentioning
confidence: 87%
“…The TCA cycle constituents ·-ketoglutarate and malate have been studied as alternative candidates as precursors for GABA, but they appear to be quantitatively less important [28][29][30][31]. In addition to be a precursor for the neurotransmitters glutamate and GABA, glutamine is oxidatively metabolized in cerebral cortical neurons [32,33] and to a lesser extent in cerebellar granule neurons [34].…”
Section: Introductionmentioning
confidence: 99%
“…However, more substantive explanations may also pertain, including the expression of other variant forms of GLT1 not yet recognized, or other transporters, such as EAAC1 (He et al, 2000), post-translational modification, or interacting proteins interfering with antibody binding. In addition, some axon terminals may use alternate pathways to resupply excitatory terminals with glutamate (Fonnum, 1984;Shank et al, 1989;Lehmann et al, 1993;Sonnewald et al, 1993;Westergaard et al, 1995;Hertz et al, 1999;Hassel and Brathe, 2000a,b).…”
Section: Glt1 Is Expressed In a Subpopulation Of Axon Terminalsmentioning
confidence: 99%